The prehistoric and late Roman settlement of Šumenje near Podturn - Breščak, Danilo; Dular, Janez (Arheološki vestnik, 2002)
This article discusses the elevated settlement of Šumenje near Podturn, which lies in the midst of the Lower Carniola hills east of Trebnje. Test excavation carried out in 1979 by the Museum of Lower Carniola in Novo mesto showed that the elevation was settled as early as the late Bronze Age, although it was not fortified with an enclosing wall. Individual finds also indicate short term settlement in the late La Tène and perhaps at the end of the Hallstatt period. In the period of late Antiquity, a small refugium was formed at Šumenje, surrounded by a wall. The entrance was discovered on the western side of the settlement.